Behavioral Components Influencing Social Development of Learners with Hearing Impairments in Public Primary Schools in Rongo Sub-County, Kenya - Mary Awino Gabriel; Rosemary Ogada; Karen Atieno Oyiengo (African Journal of Education,Science and Technology (AJEST), 2025)
In the past, people have had false and negative beliefs about disability, which has led to implications to the lives of learners with Hearing Impairment (HI). Some studies suggest that learners with HI experience isolation and do not have many friends that influence their self-confidence and social interaction capabilities. Consequently, learners with HI can holistically develop when they are taught how to socialize and equipped with necessary skills within the school environment in order to easily adapt to their daily living activities. However, enough has not been done to ensure that there is rapid socialization of learners with HI. Despite teachers attending many in-service courses, workshops and seminars organized by educational experts to improve and help unravel factors that could necessitate social development of learners with HI, such learners in public primary schools in Rongo Sub-County have not witnessed much remarkable improvements in their sociability. Hence, the purpose of this study was to investigate behavioral components influencing social development of learners with HI in public primary schools in Rongo Sub-County, Kenya. The objective of this study was to identify behavioral components influencing social development of learners with HI in the public primary schools in Rongo Sub-County, Kenya. The study was guided by Social Development Theory by Lev Vygotsky. The study utilized descriptive survey research design. The study population comprised; 50 public primary schools with special units, 50 Head Teachers (HTs), 50 Teachers of Special Needs Education (TSNE) and 63 learners with HI. Purposive sampling was used to identify 15 schools, 15 Head Teachers, 15 TSNE while all the 63 learners with HI were identified through census sampling. Quantitative data was collected using questionnaires and analyzed descriptively using SPSS version 29 into frequencies, percentages, means and Standard Deviations (SDs) and further analyzed inferentially into Pearson correlations. Qualitative data was collected using interview and observation checklist. Data from interview was analyzed thematically while data from observation checklist was analyzed descriptively into frequencies, percentages, means and SDs. Study findings were presented in the form of tables of descriptive and inferential statistics. Quantitative findings established that behavioral components had positive influence on social development r = 0.642; p<0.05. The finding was confirmed by qualitative results. Educators should use the information to discourage bullying of learners with HI and enforce social integration mechanisms through social events like sports. Teachers should advocate for peer support among learners with HI and able learners in public primary schools. The Ministry of Education (MoE), Teachers Service Commission (TSC) and Kenya Institute of Curriculum Development (KICD) should enforce inclusive and SNE to all teachers in primary schools.